(untitled) (Agro Productividad, 2024)
Objective: To assess the effect of two ovine semen diluents, Andromed® and OviXcell®, on the mass motility, vitality, and acrosomal integrity of spermatozoa processed at different temperatures and with the addition of post-thawed HTF (human tubal fluid). Design/Methodology/Approach: Semen from 2 Dorper ram was used. Four ejaculations per male were collected and diluted with Andromed® and Ovixcell®. There were four treatments with Ovixcell®: 1) fresh Ovixcell®, 2) refrigerated Ovixcell®, 3) post-thawed Ovixcell®, and 4) post-thawed Ovixcell® + HTF. Four treaments with Andromed® were also carried out: 1) fresh Andromed®, 2) refrigerated Andromed®, 3) post-thawed Andromed®, and 4) post-thawed Andromed® + HTF. Mass motility, vitality, and acrosomal integrity were performed with a CASA computer system and statistically analyzed with the GLM procedure of the SAS software. Results: When the effect of Ovixcell® mass motility was assessed, the following results were obtained, with differences (p˂0.05) between treatments: 87% in fresh semen, 72% refrigerated semen, 55% in post-thawed semen, and 68% in post-thawed semen + HTF. A clear difference (p˂0.05) was observed when HTF was added to post-thawed semen (13%). Andromed® behaved in the same way as Ovixcell® (p˂0.05) and a 18% recovery was observed with the addition of HTF. A high percentage of live spermatozoa with intact acrosome was observed for fresh semen (97.8%), while it diminished (p<0.05) as the temperature of refrigerated and frozen semen gradually decreased. Study Limitations/Implications: More experimental units should be used, despite the increase in maintenance costs per animal. Findings/Conclusions: The use of Andromed® and OviXcell® diluents was satisfactory in relation to the mass motility, vitality, and acrosomal integrity in spermatozoa processed at different temperatures (fresh, refrigerated, and post-thawed). Furthermore, the addition of HTF increased post-thawed mass motility.